Study on the Mechanical Mechanism and Prevention Method of Casing Moving up: Taking the Jidong Oilfield as an Example. (11th October 2022) - Zhou, Yan; Song, Wei; Zhao, Wanchun; Shen, Yuanyuan; Wang, Lingling; Chen, Chunlai; Zhu, Kuanliang; Pan, Junying
Abstract : In the production process of oilfields, the proportion of oil and water wells scrapped or overhauled by casing moving up continues to increase, especially in some onshore oilfields near the coast, which is more prominent. In order to clarify the causes of casing moving up and propose the treatment method of casing moving up, this paper first establishes the buckling deformation model of groundwater extraction-induced surface settlement and the buckling deformation model of casing on the surface settlement stress field and then combines the relationship between the axial jackal force generated by the buckling deformation of the casing of different well structures and the jacking strength of the casing head to give the criterion for the casting of the casing moving up. Taking Jidong Oilfield as an example, the displacement of running-up wells on 50 casings was analyzed, and the identification compliance rate reached 85.68%, and the variation law of running-up on casing with time and casing structure was given, which provided scientific guidance for subsequent casing running-up protection. Based on the model, it is concluded that enhancing the casing structure, the length of the casing cementing and sealing section, and enhancing the casing prestress are helpful for preventing the casing from moving up.